The Effect of Teacher Professionalism, Learning Infrastructure, and Work Motivation on Teacher Performance with Organizational Citizenship Behavior as a Mediation Variable at State Vocational Schools in Pangkalan Bun City - Eka Novena, Kristya Widya; Rahmawati, Tina (Universitas Muhammadiyah Pontianak, 2025)
The study aims to analyze the direct and indirect effects of teacher professionalism, learning infrastructure, and work motivation on teacher performance, mediated by organizational citizenship behavior, at State Vocational Schools in Pangkalan Bun City. This study used a quantitative method with an associative approach. The sample of this study consisted of a population of 100 teachers as the data source. Data collection techniques with questionnaire distribution. The validity test of the instrument used a convergent validity with an AVE value of > 0.5 and discriminant validity using a Fornell-Lacker value of > 0.5. The reliability of the instrument used Cronbach's alpha and composite reliability values with a construct value of > 0.7. The data analysis technique used partial least squares-structural equation modeling (PLS-SEM) with SmartPLS V.4.0.0.9 and SPSS 27. The results show that: 1) teacher professionalism has a positive and significant effect on teacher performance with a t statistics value of 3.466 and p value 0.001; 2) learning infrastructure has a positive and significant effect on teacher performance with a t statistics value of 2.258 and p value of 0.024; 3) work motivation has a positive and significant effect on teacher performance with a value of 0.024 t statistics of 2.977 and p value 0.003; 4) teacher professionalism, learning infrastructure, and work motivation have a positive and significant effect on performance with an f test value of 90.624 and a significance of 0.000; 5) OCB has a positive and significant effect of mediating the influence of teacher professionalism on teacher performance with t statistics value of 2.190 and p value 0.029; 6) OCB has a positive and significant effect of mediating the influence of learning infrastructure on teacher performance with a t statistics value of 2.351 and a p value of 0.019; and 7) OCB has a positive and significant effect of mediating the influence of work motivation on teacher performance with a t statistics value of 2.075 and p value of 0.038.